Gabriel was asked to solve x^2 - 36 = 0 by factoring using the difference of squares pattern what is/are the correct solution(s)?

1 answer

To solve the equation \( x^2 - 36 = 0 \) using the difference of squares pattern, we can recognize that it can be factored as follows:

\[ x^2 - 36 = (x - 6)(x + 6) \]

Now, we set each factor equal to zero to find the solutions:

  1. \( x - 6 = 0 \)
    This gives us \( x = 6 \).

  2. \( x + 6 = 0 \)
    This gives us \( x = -6 \).

So, the solutions to the equation \( x^2 - 36 = 0 \) are:

\[ x = 6 \quad \text{and} \quad x = -6 \]